An mTOR inhibitor discovery system using drug-sensitized yeast - Anna K. Breen; Sarah Thomas; David Beckett; Matthew Agsalud; Graham Gingras; Judd Williams; Brian M. Wasko (GeroScience, 2025)
Inhibition of the target of rapamycin (TOR/mTOR) protein kinase by the drug rapamycin extends lifespan and health span across diverse species. However, rapamycin has potential off-target and side effects that warrant the discovery of additional TOR inhibitors. TOR was initially discovered in Saccharomyces cerevisiae (yeast) which contains two TOR paralogs, TOR1 and TOR2 . Yeast lacking functional Tor1 are viable but are hypersensitive to growth inhibition by TORC1 inhibitors, which is a property of yeast that can be exploited to identify TOR inhibitors. Additionally, yeast lacking FK506-sensitive proline rotamase ( FPR1 ) or containing a tor1-1 allele (a mutation in the Fpr1-rapamycin binding domain of Tor1) are robustly and selectively resistant to rapamycin and analogs that allosterically inhibit TOR activity via an FPR1 -dependent mechanism. To facilitate the identification of TOR inhibitors, we generated a panel of yeast strains with mutations in TOR pathway genes combined with the removal of 12 additional genes involved in drug efflux. This creates a drug-sensitive strain background that can sensitively and effectively identify TOR inhibitors. In a wild-type yeast strain background, 25 µM of Torin1 and 100 µM of GSK2126458 (omipalisib) are necessary to observe TOR1 -dependent growth inhibition by these known TOR inhibitors. In contrast, 100 nM Torin1 and 500 nM GSK2126458 (omipalisib) are sufficient to identify TOR1- dependent growth inhibition in the drug-sensitized background. This represents a 200-fold and 250-fold increase in detection sensitivity for Torin1 and GSK2126458, respectively. Additionally, for the TOR inhibitor AZD8055, the drug-sensitive system resolves that the compound results in TOR1- dependent growth sensitivity at 100 µM, whereas no growth inhibition is observed in a wild-type yeast strain background. Our platform also identifies the caffeine analog aminophylline as a TOR1 -dependent growth inhibitor via selective tor1 growth sensitivity. We also tested nebivolol, isoliquiritigenin, canagliflozin, withaferin A, ganoderic acid A, and taurine and found no evidence for TOR inhibition using our yeast growth-based model. Our results demonstrate that this system is highly effective at identifying compounds that inhibit the TOR pathway. It offers a rapid, cost-efficient, and sensitive tool for drug discovery, with the potential to expedite the identification of new TOR inhibitors that could serve as geroprotective and/or anti-cancer agents.

TracMyAir smartphone application for modeling exposures to PM2.5 and ozone – Integration with air quality networks and location-activity sensors - Michael Breen; Vlad Isakov; Catherine Seppanen; Saravanan Arunachalam; Miyuki Breen; Steven Prince; Thomas Long; David Heist; Parikshit Deshmukh; K. Wyat Appel; Christian Hogrefe; Benjamin Murphy; et al. (Science of The Total Environment, 2025)

Initial impacts of the COVID-19 pandemic on Australian fisheries production, research organisations and assessment: shocks, responses and implications for decision support and resilience - Emily M. Ogier; David C. Smith; Sian Breen; Caleb Gardner; Daniel J. Gaughan; Harry K. Gorfine; Alistair J. Hobday; Natalie Moltschaniwskyj; Ryan Murphy; Thor Saunders; Mike Steer; James Woodhams (Reviews in Fish Biology and Fisheries, 2023)
Australia’s fisheries have experience in responding individually to specific shocks to stock levels (for example, marine heatwaves, floods) and markets (for example, global financial crisis, food safety access barriers). The COVID-19 pandemic was, however, novel in triggering a series of systemic shocks and disruptions to the activities and operating conditions for all Australia’s commercial fisheries sectors including those of the research agencies that provide the information needed for their sustainable management. While these disruptions have a single root cause—the public health impacts and containment responses to the COVID-19 pandemic—their transmission and effects have been varied. We examine both the impacts on Australian fisheries triggered by measures introduced by governments both internationally and domestically in response to the COVID-19 pandemic outbreak, and the countermeasures introduced to support continuity in fisheries and aquaculture production and supply chains. Impacts on fisheries production are identified by comparing annual and monthly catch data for Australia’s commercial fisheries in 2020 with averages for the last 4–5 years. We combine this with a survey of the short-term disruption to and impacts on research organisations engaged in fisheries monitoring and assessment and the adaptive measures they deployed. The dominant impact identified was triggered by containment measures both within Australia and in export receiving countries which led to loss of export markets and domestic dine-in markets for live or fresh seafood. The most heavily impact fisheries included lobster and abalone (exported live) and specific finfishes (exported fresh or sold live domestically), which experienced short-term reductions in both production and price. At the same time, improved prices and demand for seafood sold into domestic retail channels were observed. The impacts observed were both a function of the disruptions due to the COVID-19 pandemic and the countermeasures and support programs introduced by various national and state-level governments across Australia to at least partly mitigate negative impacts on harvesting activities and supply chains. These included protecting fisheries activities from specific restrictive COVID-19 containment measures, pro-actively re-establishing freight links, supporting quota roll-overs, and introducing wage and businesses support packages. Fisheries research organisations were impacted to various degrees, largely determined by the extent to which their field monitoring activities were protected from specific restrictive COVID-19 containment measures by their state-level governments. Responses of these organisations included reducing fisheries dependent and independent data collection as required while developing strategies to continue to provide assessment services, including opportunistic innovations to harvest data from new data sources. Observed short run impacts of the COVID-19 pandemic outbreak has emphasised both the vulnerability of fisheries dependent on export markets, live or fresh markets, and long supply chains and the resilience of fisheries research programs. We suggest that further and more comprehensive analysis over a longer time period of the long-run impacts of subsequent waves of variants, extended pandemic containment measures, autonomous and planned adaptive responses would be beneficial for the development of more effective counter measures for when the next major external shock affects Australian fisheries.

Trends in the abundance of Celtic Sea demersal fish: Identifying the relative importance of fishing and environmental drivers - Jed Kempf; Patricia Breen; Emer Rogan; David G. Reid (Frontiers in Marine Science, 2022)
The Celtic Sea is a productive fishing ground, therefore identifying the relative importance of fishing and environmental factors on fish stock dynamics is crucial for developing our understanding of sustainable yields and to operationalize Ecosystem Based Fisheries Management (EBFM). We investigated the effect of environmental variables and fishing on the relative abundance inferred from catch-per-unit-effort (CPUE), of twelve demersal stocks (i.e., cod, haddock, whiting, anglerfish, hake, megrim, plaice, sole, lesser-spotted dogfish, spurdog, Trisopterus spp., skates and rays) in the Celtic Sea from 1997 to 2019 (23 years). Annualized time series (1997-2019) of net primary production, bottom temperature, copepod abundance ( Calanus finmarchicus and Calanus helgolandicus ) and North Atlantic Oscillation index were used to characterize key environmental variables. Fishing exploitation rates (F/F MSY ) were used to represent fishing pressure and CPUE trends derived from an International Bottom Trawl Survey (IBTS) were used to infer abundance. We used redundancy analysis to identify key explanatory variables and then dynamic factor analysis to assess their relationships with the CPUE series and identify underlying patterns in the unexplained temporal variation. Our results show that for the majority of demersal fish species, the CPUE trends were strongly influenced by fishing exploitation rates. The gradual reduction in exploitation rates observed throughout the study period most likely led to the partial recovery of cod, spurdog, hake, megrim, plaice, whiting, Trisopterus spp., and the skates and rays. In addition, exploitation patterns on one stock influenced CPUE trends of other demersal stocks (e.g., hake, megrim, plaice, lesser-spotted dogfish, sole). We also observed that the CPUE of whiting, hake and plaice increased when C. finmarchicus were abundant in the plankton. We infer from our findings in the investigated time series that the recovery of cod, spurdog, hake, megrim, plaice, whiting, Trisopterus spp., and the skates and rays in the Celtic Sea remains dependent on controlling fishing mortality, and this would not, at least for now, be confounded by the environmental conditions.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Phototactic tails: Evolution and molecular basis of a novel sensory trait in sea snakes - Jenna M. Crowe‐Riddell; Bruno F. Simões; Julian C. Partridge; David M. Hunt; Steven Delean; Julian G. Schwerdt; James Breen; Alastair Ludington; David J. Gower; Kate L. Sanders (Molecular Ecology, 2019)
Dermal phototaxis has been reported in a few aquatic vertebrate lineages spanning fish, amphibians and reptiles. These taxa respond to light on the skin of their elongate hind‐bodies and tails by withdrawing under cover to avoid detection by predators. Here, we investigated tail phototaxis in sea snakes (Hydrophiinae), the only reptiles reported to exhibit this sensory behaviour. We conducted behavioural tests in 17 wild‐caught sea snakes of eight species by illuminating the dorsal surface of the tail and midbody skin using cold white, violet, blue, green and red light. Our results confirmed phototactic tail withdrawal in the previously studied Aipysurus laevis , revealed this trait for the first time in A. duboisii and A. tenuis , and suggested that tail photoreceptors have peak spectral sensitivities between blue and green light (457–514 nm). Based on these results, and an absence of photoresponses in five Aipysurus and Hydrophis species, we tentatively infer that tail phototaxis evolved in the ancestor of a clade of six Aipysurus species (comprising 10% of all sea snakes). Quantifying tail damage, we found that the probability of sustaining tail injuries was not influenced by tail phototactic ability in snakes. Gene profiling showed that transcriptomes of both tail skin and body skin lacked visual opsins but contained melanopsin ( opn4x ) in addition to key genes of the retinal regeneration and phototransduction cascades. This work suggests that a nonvisual photoreceptor (e.g., Gq rhabdomeric) signalling pathway underlies tail phototaxis, and provides candidate gene targets for future studies of this unusual sensory innovation in reptiles.

Stakeholders and social networks identify potential roles of communities in sustainable management of invasive species - Harriet A. Omondiagbe; David R. Towns; Jay K. Wood; Barbara Bollard-Breen (Biological Invasions, 2017)

Comment on “Population dynamics reveal conservation priorities of the threatened New Zealand sea lion Phocarctos hookeri” by Meyer, Robertson, Chilvers and Krkošek (2015) - David A. J. Middleton; Paul A. Breen (Marine Biology, 2016)

Genomics in a changing arctic: critical questions await the molecular ecologist - Stan D. Wullschleger; Amy L. Breen; Colleen M. Iversen; Matthew S. Olson; Torgny Näsholm; Ulrika Ganeteg; Matthew D. Wallenstein; David J. Weston (Molecular Ecology, 2015)
Molecular ecology is poised to tackle a host of interesting questions in the coming years. The Arctic provides a unique and rapidly changing environment with a suite of emerging research needs that can be addressed through genetics and genomics. Here we highlight recent research on boreal and tundra ecosystems and put forth a series of questions related to plant and microbial responses to climate change that can benefit from technologies and analytical approaches contained within the molecular ecologist's toolbox. These questions include understanding (i) the mechanisms of plant acquisition and uptake of N in cold soils, (ii) how these processes are mediated by root traits, (iii) the role played by the plant microbiome in cycling C and nutrients within high‐latitude ecosystems and (iv) plant adaptation to extreme Arctic climates. We highlight how contributions can be made in these areas through studies that target model and nonmodel organisms and emphasize that the sequencing of the Populus and Salix genomes provides a valuable resource for scientific discoveries related to the plant microbiome and plant adaptation in the Arctic. Moreover, there exists an exciting role to play in model development, including incorporating genetic and evolutionary knowledge into ecosystem and Earth System Models. In this regard, the molecular ecologist provides a valuable perspective on plant genetics as a driver for community biodiversity, and how ecological and evolutionary forces govern community dynamics in a rapidly changing climate.

Oligoamides of 2-amino-5-alkylthiazole 4-carboxylic acids: anti-trypanosomal compounds - Stuart Lang; Abedawn I. Khalaf; David Breen; Judith K. Huggan; Carol J. Clements; Simon P. MacKay; Colin J. Suckling (Medicinal Chemistry Research, 2014)

Comment on sea lion population viability analysis - Paul A. Breen; David J. Gilbert; Paul J. Starr (Polar Biology, 2012)

Genetic consequences of glacial survival: the late Quaternary history of balsam poplar ( Populus balsamifera L.) in North America - Amy L. Breen; David F. Murray; Matthew S. Olson (Journal of Biogeography, 2012)
Aim Beringia, the unglaciated region encompassing the former Bering land bridge, as well as the land between the Lena and Mackenzie rivers, is recognized as an important refugium for arctic plants during the last ice age. Compelling palaeobotanical evidence also supports the presence of small populations of boreal trees within Beringia during the Last Glacial Maximum. The occurrence of balsam poplar ( Populus balsamifera ) in Beringia provides a unique opportunity to assess the implications of persistence in a refugium on present‐day genetic diversity for this boreal tree species. Location North America. Methods We sequenced three variable non‐coding regions of the chloroplast genome (cpDNA) from 40 widely distributed populations of balsam poplar across its North American range. We assessed patterns of genetic diversity, geographic structure and historical demography between glaciated and unglaciated regions of the balsam poplar’s range. We also utilized a coalescent model to test for divergence between regions. Results Levels of genetic diversity were consistently greater for populations at the southern margin (θ W = 0.00122) than in the central (θ W = 0.00086) or northern (θ W = 0.00034) regions of the current distribution of balsam poplar, and diversity decreased with increasing latitude ( R 2 = 0.49, P 0.01). We detected low, but significant, structure ( F CT = 0.05, P = 0.05), among regions of P. balsamifera ’s distribution. The cpDNA genealogy was shallow, however, showing an absence of highly differentiated chloroplast haplotypes. Coalescent analyses supported a model of divergence between the southern ice margin and the northern unglaciated region of balsam poplar’s distribution, but analyses of other regional comparisons did not converge. Main conclusions The palaeobotanical record supports the presence of a Beringian refugium for balsam poplar, but we were unable to definitively identify the presence of known refugial populations based on genetic data alone. Balsam poplar populations from Beringia are not a significant reservoir of cpDNA diversity today. Unique alleles that may have been present in the small, isolated populations that survived within Beringia were probably lost through genetic drift or swamped by post‐glacial, northward migration from populations south of the ice sheets.

Influence of genetic background on tumor karyotypes: Evidence for breed-associated cytogenetic aberrations in canine appendicular osteosarcoma - Rachael Thomas; Huixia J. Wang; Pei-Chien Tsai; Cordelia F. Langford; Susan P. Fosmire; Cristan M. Jubala; David M. Getzy; Gary R. Cutter; Jaime F. Modiano; Matthew Breen (Chromosome Research, 2009)

MRI-guided Thermal Ablation Therapy: Model and Parameter Estimates to Predict Cell Death from MR Thermometry Images - Michael S. Breen; Miyuki Breen; Kim Butts; Lili Chen; Gerald M. Saidel; David L. Wilson (Annals of Biomedical Engineering, 2007)

The effects of chronic nicotine on spatial learning and bromodeoxyuridine incorporation into the dentate gyrus of the rat - Charles Scerri; Caroline A. Stewart; Kieran C. Breen; David J. K. Balfour (Psychopharmacology, 2006)

Estimated Ultraviolet Radiation Doses in Wetlands in Six National Parks - Stephen A. Diamond; Peter C. Trenham; Michael J. Adams; Blake R. Hossack; Roland A. Knapp; Stacey L. Stark; David Bradford; P. Stephen Corn; Ken Czarnowski; Paul D. Brooks; Dan Fagre; Bob Breen; et al. (Ecosystems, 2005)

Three-Dimensional Registration of Magnetic Resonance Image Data to Histological Sections with Model-Based Evaluation - Michael S. Breen; Roee S. Lazebnik; David L. Wilson (Annals of Biomedical Engineering, 2005)

Canine TCOF1; cloning, chromosome assignment and genetic analysis in dogs with different head types - Kim E. Haworth; Ira Islam; Matthew Breen; Wendy Putt; Eleni Makrinou; Matthew Binns; David Hopkinson; Yvonne Edwards (Mammalian Genome, 2001)

Apolipoprotein-E dependent role for the FAS receptor in early onset Alzheimer's disease: finding of a positive association for a polymorphism in the TNFRSF6 gene - Lars Feuk; Jonathan Prince; Gerome Breen; Tesfai Emahazion; Andrew Carothers; David St Clair; Anthony Brookes (Human Genetics, 2000)